PENGENALAN APLIKASI PENDUKUNG PJJ - Sartika Lina Mulani Sitio; Irpan Kusyadi Kusyadi; Mohadib Mohadib Mohadib; Teti Desyani Desyani; Ahmad Arifin Arifin (KOMMAS: Jurnal Pengabdian Kepada Masyarakat, 2021)
Distance learning or more often called PJJ, is a distance learning activity carried out by most schools around the world. PJJ is held and implemented to prevent the transmission of the Covid-19 virus in various regions of the world, one of which is in Indonesia. PJJ is also one of the efforts of the education world in continuing to create quality successors of the nation, but still keeping them from contracting the Covid-19 virus. Starting Monday, March 16, 2020 until now, teaching and learning activities no longer take place face-to-face in schools, but through Distance Learning (PJJ). Students learn from home with guidance from teachers and parents. The Computer-Based National Standard Madrasah Final Examination (UAMBNBK) activity which was supposed to be held for three days from March 16-18, 2020 was canceled. The school has begun to arrange appropriate learning strategies to deal with the pandemic. At the beginning of the pandemic, the media (application) used for online learning was WhatsApp. The obstacles faced are limited human resources, limited infrastructure such as laptops or cellphones owned by parents of students, difficulties in internet access, unstable electricity conditions, and limited internet quotas that can be provided by parents. This PKM activity is expected to be sustainable at Arraisiyah Vocational School, South Tangerang with a different theme. Keywords: Learning; Aplikasi; Long Distance.